Rethinking Participation Research in Adult Education: International Perspectives - Sean Courtney; Veronica McGivney; John Mcintyre; Kjell Rubenson (Adult Education Research Conference, 1998)
The purpose of this symposium is to analyze research on participation in adult education from an international perspective. Panelists will discuss findings from their respective parts of the world and consider how research and theory on this important phenomenon can be advanced.